Makna Lagu “Tikus-Tikus Kantor” Oleh Iwan Fals - Eef Rokhmansyah (Pusat Riset dan Inovasi Nasional, 2023)
This article analyzes the interpretations and metaphors on the lyric of Iwan Fals song. This research was also conducted using the hermeneutic approach which showed that is was descriptive. There are also metaphors used in the